Some aspects of the biology of Nile perch, Lates niloticus, in the open waters of Lake Victoria, Kenya. Issue 3 (14th September 2017) - Yongo, Edwine; Outa, Nicholas; Kito, Keiko; Matsushita, Yoshiki
Abstract: Samples (6404) of Nile perch were collected monthly from commercial catches between June 2014 and June 2015. The total length (cm), weight (g) and sex of fish were all determined in the field, with 3771 (59%) being male and 2059 (32%) being female fish, for an overall sex ratio of 1.83:1.00 (male: female). The average length and weight for all fish were 55.38 ± 0.14 cm TL and 2355.10 ± 22.30 g, respectively. The size of male fish ranged from 15.5 to 128.5 cm TL and weighed between 190 and 25 000 g, whereas that of female ranged from 21.0 to 130.0 cm TL and weighed between 124 and 25 800 g. The value of the regression slope b of the length–weight relationship was equal to 3.04. The mean (±SD) condition factor for all fish was 1.23 ± 0.13. The condition factor was different in the length groups, with the highest (1.32 ± 0.13) and lowest (1.12 ± 0.20) values recorded in length groups 100–110 and <30 cm TL, respectively. The highest and lowest condition factors were recorded between January and March, respectively. The length–weight relationship and condition of Nile perch in Lake Victoria have deteriorated greatly, this finding being linked to the reduction of its prey species in the lake.